2020
DOI: 10.1155/2020/9196379
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Key MicroRNAs Targeted by Narenmandula in a Rodent Nephropathy Model

Abstract: Background. Untreated nephropathy can progress to renal failure. The traditional Mongolian remedy Narenmandula regulates the kidney “yang.” This study aimed to identify key microRNAs (miRNAs) targeted by Narenmandula in a rat model of nephropathy. Methods. Fifteen rats exhibiting normal renal function were randomized to three study arms. Nephropathy was induced in n = 10 rats using doxorubicin hydrochloride, followed by either Narenmandula treatment (treatment group) or no treatment (control group). In n = 5 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Finally, among 24 candidate miRNAs, we found two miRNAs, miR-34a-5p and miR-452-5p, which showed the most significant regulatory effects on their target genes. These two miRNAs have previously been reportedly found in the lung [26][27][28], liver [28,29], kidney [30,31], and a certain type of cancer cells [32,33]. In recent studies, miR-34a-5p has been found to mediate the lipotoxic effect of pancreatic β-cells in hyperlipidemia mice [34], while miR-452-5p has been reported to be involved in the tumorigenesis especially reproductive endocrine tumors such as prostate cancer [35] and breast cancer [36].…”
Section: Discussionmentioning
confidence: 94%
“…Finally, among 24 candidate miRNAs, we found two miRNAs, miR-34a-5p and miR-452-5p, which showed the most significant regulatory effects on their target genes. These two miRNAs have previously been reportedly found in the lung [26][27][28], liver [28,29], kidney [30,31], and a certain type of cancer cells [32,33]. In recent studies, miR-34a-5p has been found to mediate the lipotoxic effect of pancreatic β-cells in hyperlipidemia mice [34], while miR-452-5p has been reported to be involved in the tumorigenesis especially reproductive endocrine tumors such as prostate cancer [35] and breast cancer [36].…”
Section: Discussionmentioning
confidence: 94%
“…According to Wilting et al, chromosomal instability alters miRNA expression at different stages of cancer growth [ 48 ]. Studies suggest a correlation between viral oncoproteins and the dysregulation of miRNAs in various stages of cervical dysplasia, which may contribute to the development and progression of CC [ 49 ]. HPV-induced cell transformation requires the viral oncoproteins E6 and E7.…”
Section: Discussionmentioning
confidence: 99%
“…According to Wilting et al, chromosomal instability alters miRNA expression at different stages of cancer growth (46). Studies suggest a correlation between viral oncoproteins and the dysregulation of miRNAs in various stages of cervical dysplasia, which may contribute to the development and progression of CC (47). HPV-induced cell transformation requires the viral oncoproteins E6 and E7.…”
Section: Discussionmentioning
confidence: 99%